Learning the carnatic music composition varnam in the time signature 3/4 - Darshanan, S.; Hamsathvani, H. (university of Jaffna, 2014)
The Carnatic music is divided in to two major divisions as taught compositions and improvisation of music. This research focuses on the first part, the taught compositions, because the improvisation of music is almost not based on the knowledge, which is given by the teacher. It is mainly based on the skills of the learner. Among the taught compositions, The Varnam is the most significant composition. This is being taught in the schools and universities which provide carnatic music education and training; as well as performing in the concerts. But, the results from the pilot study say that performing the varnam in the time signature 3/4 is the most difficult activity in carnatic music, in students' perspective. Therefore, this research is to test the hypothesis “The Most complicated learning process in Carnatic music is performing varnam in the time signature 3/4.” The questionnaire survey method is appointed for this research. The results of the survey analysis supported the hypothesis. The conclusion is derived that the significant importance is not given to the teaching and learning process in the performing Varnam in the time signature 3/4. The research recommends adopting the modern techniques and instruments in the teaching and learning process of the performing varnam in the time signature 3/4.
Keywords: Music composition; Varnam; Carnatic music teaching; Carnatic music learning; Complicated compositions; Modern teaching techniques